Gout and the risk of epilepsy: A population-based cohort study. Issue 26 (26th June 2020) - Chen, Hung-Lin; Hsu, Yi-Chao; Chen, Chang-Hsu; Wang, Pei-Jen; Lin, Cheng-Li; Cheng, Sheng-Han; Chang, Kuang-Hsi
Abstract : Abstract: Gout is a chronic disease related to uric acid metabolism. It involves crystals of uric acid accumulating in the joints, causing joint pain and releasing cytokines that trigger inflammation. Inflammation is a key component in the pathogenesis of epilepsy. Thus, we conducted a cohort study to investigate if epilepsy is associated with gout and determine the risk of epilepsy in patients with gout. The gout cohort was obtained from the Registry of Catastrophic Illnesses Patient Database (RCIPD). We identified 104, 238 patients who were aged 20 years or more and newly diagnosed with gout between 2000 and 2011 and 3 outpatient visits or history of gout-specific hospitalization between 2000 and 2011. Patients without gout were frequency matched with the gout cohort at a 2:1 ratio according to age, sex, comorbidities, and year of gout diagnosis. The gout cohort showed a 1.27-fold higher overall crude hazard ratio (HR) for epilepsy compared with the control cohort. After we adjusted the analyses by age, sex, and comorbidities the gout patients displayed an increased risk of epilepsy compared with the control group (adjusted HR = 1.25, 95% confidence interval = 1.15–1.36). This study revealed a significantly higher risk of epilepsy in patients with gout. It provides further evidence for the debate around the effect of gout on brain health.